Efficacy of maintenance treatment in patients with multiple myeloma: a systematic review and network meta-analysis. Issue 1 (31st December 2022) - Zhi, Yongjin; Bao, Shuojing; Mao, Jingcheng; Chai, Gufan; Zhu, Jianfeng; Liu, Chengjiang; Chen, Xi
ABSTRACT: Background: Despite conspicuous advances in innovating novel drugs and combination regimens in multiple myeloma (MM) in recent decades, the most appropriate maintenance regimens after inductive therapy are still controversial and opaque. Objective: We aimed to identify the most effective maintenance treatment for newly diagnosed multiple myeloma (NDMM) patients via network meta-analysis. Method: We searched PubMed, Embase, Cochrane Library, Scopus, and Google Scholars from inception to April, 2022. Odds ratios (ORs) were generated for dichotomous variants. The primary endpoint was overall survival (OS). Results: Eventually a total of 19 trials, including 11 treatments and 8337 patients, were included in this analysis. For OS, lenalidomide (OR ranged from 1.61 to 1.99) and daratumumab (OR ranged from 1.83 to 2.41) showed significant efficacy over placebo. Maintenance therapy comprising lenalidomide-carfilzomib (OR ranged from 3.19 to 6.95), lenalidomide-prednisone (OR ranged from 2.62 to 4.44), bortezomib-thalidomide (OR ranged from 2.48 to 3.64), daratumumab (OR ranged from 2.0 to 2.98), lenalidomide (OR ranged from 1.4 to 3.19), ixazomib (OR ranged from 1.36 to 2.05), thalidomide (OR ranged from 1.5 to 1.86) demonstrated significant effects in prolonging PFS compared with placebo; Among the efficient therapies, lenalidomide-carfilzomib was significantly superior to lenalidomide (OR ranged from 2.18 to 2.20), daratumumab (OR ranged from 1.49 to 2.66) and ixazomib (OR ranged from 2.75 to 3.57). Conclusion: Considering OS and PFS, lenalidomide-carfilzomib should be recommended as the best therapy. In clinical practice, this must be weighed against the increased risk of adverse events and financial burden. However, more head-to-head studies are needed to confirm these findings.